2004
DOI: 10.1042/bj20031157
|View full text |Cite
|
Sign up to set email alerts
|

HNF1alpha is involved in tissue-specific regulation of CFTR gene expression

Abstract: The CFTR (cystic fibrosis transmembrane conductance regulator) gene shows a complex pattern of expression with tissue-specific and temporal regulation. However, the genetic elements and transcription factors that control CFTR expression are largely unidentified. The CFTR promoter does not confer tissue specificity on gene expression, suggesting that there are regulatory elements outside the upstream region. Analysis of potential regulatory elements defined as DNase 1-hypersensitive sites within introns of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 44 publications
(58 reference statements)
7
64
0
Order By: Relevance
“…We would predict that removal of multiple enhancer sites and the promoter would be required to completely extinguish CFTR expression in any epithelial cell type. We demonstrate here that one of the tissue-specific transcription factors interacting with the enhancers in intestinal cells is HNF1, which we have previously shown to be involved in CFTR expression both in vitro and in vivo through interactions at multiple intronic sites (27,28). HNF1 has been implicated in a similar mechanism of transcriptional regulation in the human ADH gene, where it binds a distal enhancer and augments gene expression (34).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We would predict that removal of multiple enhancer sites and the promoter would be required to completely extinguish CFTR expression in any epithelial cell type. We demonstrate here that one of the tissue-specific transcription factors interacting with the enhancers in intestinal cells is HNF1, which we have previously shown to be involved in CFTR expression both in vitro and in vivo through interactions at multiple intronic sites (27,28). HNF1 has been implicated in a similar mechanism of transcriptional regulation in the human ADH gene, where it binds a distal enhancer and augments gene expression (34).…”
Section: Discussionmentioning
confidence: 93%
“…Additional cell-line specific DHS are evident in intron 10 (1716 ϩ 13.2 kb) in Caco2 cells and intron 18 (3600 ϩ 1.6 kb) in HT29. The intron 10 site encompasses two closely spaced DHS at 1716 ϩ 13.2 kb and ϩ13.7 kb, that were characterized in our previous work (22,23,28). Also of interest are the DHS located -35 kb and -44 kb with respect to the CFTR translational start site in primary epididymis cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Alternatively, ATP8B1 defect could affect the transcriptional activity not only of FXR, 13 but also of other transcription factors, like HNF1, which regulate the tissue-specific expression of CFTR. 40 Because CFTR is a major determinant of hydroelectrolytic secretion in the biliary tract, 20,[41][42][43] CFTR downregulation may contribute to impaired bile secretion through bile inspissation in PFIC1. This would explain the typical ultrastructural abnormality of bile in PFIC1 termed "Byler bile", characterized by a coarsely granular appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these two proteins are also expressed in the intestinal epithelium but little is known about their function in this organ. To date, several studies have demonstrated that these transcription factors activate the expression of a number of intestinal genes including Fabp1, LPH, Cftr and Glc-6-Pase, which are expressed in differentiated enterocytes (Mouchel et al, 2004;Gautier-Stein et al, 2006;Bosse et al, 2007). An in vitro study demonstrated that Hnf1a and b control the transcription of Dpp4, another marker of differentiated enterocytes (Erickson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%